Advances in polycyclization cascades in natural product synthesis. (23rd November 2020) - Jiang, Yubo; McNamee, Ryan E.; Smith, Philip J.; Sozanschi, Ana; Tong, Zixuan; Anderson, Edward A.
Abstract : Cascade reactions are among the most powerful means to achieve the construction of multiple ring systems in a single step. This tutorial review describes recent advances in the use of polycyclization cascades in natural product synthesis. Abstract : Cascade reactions (also known as domino reactions) are arguably the most powerful means to achieve the construction of multiple ring systems in a single step. In this Tutorial Review, highlights in cascade polycyclizations applied to natural product syntheses over the last five years are discussed, including pericyclic, ionic, metal-catalyzed, organocatalytic, and radical processes. Significant developments in each of these fields that have advanced the state-of-the-art are a particular focus, including photochemical and electrochemical methods, novel biomimetic routes, and enantioselective cascades.